2020
DOI: 10.1093/gji/ggaa452
|View full text |Cite
|
Sign up to set email alerts
|

Time-lapse CSEM: how important is survey repeatability?

Abstract: Summary An important concern for time-lapse studies using the controlled-source electromagnetic (CSEM) method is repeatability of acquisition parameters for the base and monitoring surveys. We consider a challenging case when variations in source and receiver positions, conductivity of seawater etc. will lead to differences in the recorded EM fields that exceed EM response due to production-induced changes in the reservoir resistivity. We show that even in that case, 4D response can often be cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…CSEM time-lapse studies can be sorted into two main groups: data-domain studies, where CSEM datasets from base and monitoring surveys are directly compared [36,37], and model-domain studies, where a comparison is made by using the recovered models for each survey [16,18]. The latter approach's main advantage is that it avoids or minimizes the need for strict repeatability requirements when analyzing the 4D response in the data domain.…”
Section: Marlim Time-lapse Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…CSEM time-lapse studies can be sorted into two main groups: data-domain studies, where CSEM datasets from base and monitoring surveys are directly compared [36,37], and model-domain studies, where a comparison is made by using the recovered models for each survey [16,18]. The latter approach's main advantage is that it avoids or minimizes the need for strict repeatability requirements when analyzing the 4D response in the data domain.…”
Section: Marlim Time-lapse Modelmentioning
confidence: 99%
“…In the present work, we extend the findings of [18] in monitoring the effects of CSEM due to changes in resistivity resulting from water saturation changes within the reservoir. Other effects will not be considered, as they have been thoroughly examined by [16].…”
Section: Marlim Time-lapse Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that the resistivity changes are only associated with the fluid substitution within the reservoir's boundaries (Figure 3a), while the background resistivity remains unchanged. Other superficial effects are not considered as they have been thoroughly investigated by [2].…”
Section: Marlim R3d (Mr3dmentioning
confidence: 99%
“…Ongoing development efforts have demonstrated the potential to enhance cost-effective deep-water reservoir-monitoring applications. Indeed, several pioneering feasibility studies (e.g., [1][2][3]) have revealed that time-lapse (4D) CSEM can play a role in improving our knowledge of the reservoir structure, fluid flow, and fluid saturation changes when appropriate acquisition and advanced integrated interpretation workflows are applied.…”
Section: Introductionmentioning
confidence: 99%